Analisis Kemampuan Penalaran Matematis Siswa Dalam Menyelesaikan Soal Cerita Matematika di MTs Negeri 5 Merangin - Ratna Apriyani; Gugun M Simatupang; Feri Tiona Pasaribu (Universitas Veteran Bangun Nusantara, 2021)
In this study, the ability of mathematical reasoning is measured based on its indicators, namely, drawing logical conclusions, providing explanations with models, facts, characteristics or relationships, estimating answers and solution processes and formulating valid arguments. This type of research is qualitative research using a descriptive approach. The research was conducted at MTs Negeri 5 Merangin. The subjects used in this study were 3 students who were taken from class VII-B.The results showed that students who have mathematical reasoning abilities SKP-01 have been able to meet all indicators of mathematical reasoning abilities. SKP-02 students with mathematical reasoning abilities are unable to meet the indicators of compiling valid arguments. And SKP-03 students are not able to meet the indicators of estimating the answer and the solution process and the indicators compile valid arguments. So the three subjects who have different mathematical reasoning abilities, have obstacles in fulfilling different mathematical ability indicators.Thus, efforts to improve children's abilities in learning mathematics, especially in their mathematical reasoning abilities, require the selection of appropriate learning methods, encouraging students to interact positively with fellow students and with teachers when learning, encouraging students to use logical reasoning in solving math problems.